ESTIMATION OF NEONATAL WEIGHT CHANGE ACCORDING TO THE ADEQUACYOF GESTATIONAL WEIGHT GAIN IN PREGNANT WOMEN AT MARÍA AUXILIADORAHOSPITAL, 2022–2024 - Carranza Aldana , Angello Miguel (2025)
Introduction. Maternal weight directly influences fetal growth and neonatal birthweight, with important implications for perinatal health. Objective. To estimate the variation in neonatal birthweight according to the adequacy of gestational weight gain among Peruvian pregnant women. Methods. An analytical, cross-sectional, and retrospective study was conducted at Hospital María Auxiliadora between July 2022 and July 2024. Singleton, term newborns with recorded birth weight and complete maternal data were included, excluding multiple pregnancies and preterm or post-term deliveries. The minimum sample size was 196 neonates. The dependent variable was the difference in grams relative to 4,000 g, and the main independent variable was the difference in kilograms compared to the gestational weight gain recommended by the Institute of Medicine. Multiple linear regression was applied, adjusted for previous macrosomia, sex, maternal age, and prenatal care, with significance set at p<0.05. Results. Of the 196 neonates, 59.7% were male, and 70.6% of mothers were under 35 years old. Adequate prenatal care was reported in 90.3% of cases, and 11.8% had a history of macrosomia. For each additional kilogram of weight gained above the recommended level, neonatal weight increased by an average of 39.3 g (95% CI: 20.9–57.8; p<0.001). Previous macrosomia increased neonatal weight by 590.4 g (95% CI: 327.4–853.3; p<0.001). No significant associations were found with sex, maternal age, or prenatal care. Conclusions. Excessive gestational weight gain and a history of macrosomia are associated with higher neonatal weight, underscoring the importance of individualized prenatal care.